Konsep Pembelajaran Menyenangkan bagi Siswa Kelas Bawah Tingkat Sekolah Dasar - Erna Rahmawati (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
Fun learning is a method of learning that uses a basic needs-based approach for lower-class students. Fun learning is needed especially for lower-class students who have characteristics: a lot of moving, requiring a lot of teacher attention and a lot of introducing new things for students with a tendency to a limited level of concentration of lower grade students. This fun learning is an urgent need in this modern era. Therefore, this study aims to explain the concept of fun learning, especially for elementary school students (grades 1-3) elementary school level. The methodology used in this research uses a type of qualitative research with an analytical descriptive approach. The results showed that the concept of learning fun for elementary school lower class students should be based on the needs of lower-class students who prioritize motor movement over cognitive, explain the material in a visual way rather than auditory, involve students in the learning process (two-way learning rather than one-way), and include elements of games in learning.